HERBICIDAL ACTIVITY OF FUNGAL CULTURE FILTRATES AGAINST CHENOPODIUM ALBUM L.AND AVENA FATUA L. - M. Akbar; A. Javaid (Journal of Animal and Plant Sciences, 2012)
Culture filtrates of four Drechslera spp. namely D.  hawaiiensis M.B. Ellis, D. holmii (Luttr.) Subramanian and Jain, D. biseptata (Sacc. and Roum.) Richardson and Fraserand D. australiensis (Bugnicourt) Subramanian and Jain., were evaluated for their herbicidal activity against two cumbersome weeds of wheat (Triticum aestivum L.) namely Chenopodium album L. (dicot) and Avena fatua L. (monocot). Culture filtrates of these fungal species were prepared in M-1-D medium. In in vitro bioassays, the effect of original (100%) and diluted (50%) fungal culture filtrates were investigated in Petri plates against different growth parameters of the two test weed species and a wheat var. Inqlab- 91. Culture filtrates of all the four Drechslera species appreciably reduced germination as well as root/shoot growth of C. album and A. fatua. All the fungal culture filtrates also suppressed root/shoot growth of wheat; however, the effect was less intense as compared to the effect against the two weed species. In foliar spray bioassays, the effect of original culture filtrates was studied on the growth of 1-week and 2-weeks old weeds and wheat plants. Culture filtrate of D. hawaiiensis significantly reduced the shoot and root biomass of 1-week old plants of C. album. Similarly, the culture filtrates of D. biseptata and D. australiensis significantly suppressed shoot biomass of both 1-week and 2-weeks old A. fatua plants. None of the fungal culture filtrates exhibited significant effect on shoot and root biomass of wheat in foliar spray bioassays.
Keywords: Avena fatua; Chenopodium album; Drechslera spp. fungal culture filtrates; natural herbicides; weeds of